TIME-DEPENDENT RELIABILITY ANALYSIS OF FANS IMPELLER STRUCTURE BASED ON THE PROBABILITY DENSITY EVOLUTION THEORY (MT) - FAN XuMing; LI CeCe; WANG YingJian; YANG HuanHong; ZHANG Liang; ZHANG Shuang (Jixie qiangdu)
To efficiently evaluate the dynamic reliability of the impeller structure in cross-flow fans, its probability density function of maximal stress is established using the probability density evolution theory（PDEM）. The stochastics in structure and surroundings are considered and the finite element analysis model is used. On the basis, the structural failure probability and time-dependent reliability at different operation times are given. The Abaqus finite element analysis software is developed again. Through the joint simulation of Matlab and Abaqus, the whole process batch simulation analysis of model building, stress analysis, result extraction and probability density evolution is realized. By comparing with the agent model method and the Monte-Carlo model from the perspectives of calculation efficiency and accuracy, the practicability of PDEM in evaluating the dynamic reliability of impeller structure is further validated.